Pulmonary physical therapy techniques for the management of COVID-19 patients: a systematic review - Khan, Savera; Zaidi, Syeda Ayman; Aatik Arsh; Haleem, Muhammad Hamad (Journal of the Pakistan Medical Association, 2022)
Objective: To review studies reporting pulmonary physical therapy techniques for the management of coronavirus disease-2019 patients. Method: The systematic review was conducted according to Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines Comprised search of MEDLINE via PubMed, Physiotherapy Evidence Database (PEDro), Excerpta Medica Database (EMBASE), Allied and Complementary Medicine Database (AMED) and Cumulated Index to Nursing and Allied Health Literature (CINHAL) for Observational and interventional studies published in English language between December 2019 and January 2022 describing pulmonary physical therapy techniques for the management of coronavirus disease-2019 patients. Google Scholar and reference lists of relevant studies were also searched to identify additional articles. Methodological quality of the included studies was assessed using either the Physiotherapy Evidence Database (PEDro) scale for interventional studies or the National Institutes of Health quality assessment tool for observational studies. Results: Of the 3767 studies found, 17(0.45%) were analysed; 13(76.5%) observational and 4(23.5%) interventional. The most common pulmonary physical therapy techniques used were active cycle of breathing techniques, positive expiratory pressure device, breathing exercises, percussions, and chest abdomen muscle exercises. However, majority of the studies applied prone positioning and suctioning as priority treatment. During mechanical ventilation, mucus clearance and alveolar recruitment manoeuvres were commonly applied. Conclusion: There was scarcity of high-quality studies regarding the use of different pulmonary physical therapy techniques in coronavirus disease-2019 patients. Based on available literature, different techniques can be used, depending on stage and severity of the disease. Key Words: COVID-19, Physical therapy, Pulmonary, Rehabilitation, Techniques.